Technical Assistance Services of the international Monetary Fund. (Pamphlet Series, 1979)
This paper discusses technical assistance services of the IMF. The technical assistance and advice provided by the IMF to its members are an integral part of its activities. They may take many forms, operate at all levels of authority, and cover a wide array of topics, ranging from broad policy issues to narrow technical problems. Much of the general technical assistance provided by the IMF is a product of its regular annual consultations with members. These consultations provide an occasion for review and appraisal of the country's economic and financial situation and also an opportunity for the member to draw upon the expertise of the IMF's staff for advice and assistance.